Endogenous forms of ATP–ATP 4− and MgATP 2− —orchestrate distinct pathophysiological signaling via biased activation of P2X3 receptors - Jin Wang; Li Guan; Ting-Ting Wang; Tang-Xuan Xie; Yi-Yu Lin; Meng-Yang Sun; Dong-Ping Wang; Xue Zhang; Yu-Jing Bian; Chen-Xi Yue; Bei-Bei Ding; Xue-Fei Ma; et al. (Proceedings of the National Academy of Sciences, 2025)
P2X receptors, a family of ATP-activated ion channels, encompass subtypes P2X1–7, which are expressed in both homo- and heterotrimeric forms across various tissues. These receptors play crucial roles in pathophysiological processes such as synaptic transmission, nociception, cough, and taste perception. Extracellular ATP exists as both MgATP 2− and ATP 4− , with P2X3 responding to both. The evolutionary rationale for two nearly identical ligands and their distinct signaling potential remains unclear. While previous structural studies suggest a uniform ATP recognition mechanism for two endogenous ATP forms, we propose that MgATP 2− and ATP 4− activate P2X3 through distinct mechanisms, leading to differential physiological and pathological outcomes. Using mutagenesis, voltage-clamp fluorometry, and small molecule interventions, we identify divergent interactions of ATP 4− and MgATP 2− with P2X3, despite binding to the same orthosteric pocket. In P2rx3 D158A/D158A transgenic mice, which selectively impair MgATP 2− activation, we find that MgATP 2− modulates ammonia-induced cough frequency without affecting complete Freund’s adjuvant-induced inflammatory pain or sweet taste preference. P2rx3 −/− mice show deficits in all three responses. The allosteric inhibitor aurintricarboxylic acid selectively modulates ATP 4− and MgATP 2− effects, resulting in distinct antitussive and analgesic outcomes in vivo. These findings uncover a mechanism of P2X3 activation by its endogenous ligands, diverging from previous structural models and resembling the biased activation mechanisms observed in G-protein-coupled receptors, offering insights for P2X3-targeted therapeutics.